Speak for yourself : writing with voice - Rubenstein, Susanne, 1954- (National Council of Teachers of English, 2018)
"Acknowledges that standardized writing instruction has silenced student voices and challenges teachers to create writing classrooms in which students take ownership of their work, enjoy what they're writing, and produce writing that shows depth of thought and originality of expression"--